Establishing a Hypertension Referral Program for Uninsured Patients to a Student-Run Free Clinic - Sydney Bormann; Riley Paulsen; Narysse Nicolet; Daniel Schmidtman; Luke Hurley; Evan Meyer; Nicole Rogers; Austin Benson; Mark Beard; Mamoon Ahmed (Journal of Student-Run Clinics, 2025)
Introduction: Hypertension disproportionately impacts uninsured populations. Medical students from the University of South Dakota Sanford School of Medicine initiated weekly blood pressure (BP) screenings at The Banquet, a free meal service, finding that guests rarely followed up with primary care despite hypertensive readings. This project established a referral pathway to the Coyote Clinic, a student-run free clinic, alongside a volunteer outreach program.Methods: Medical students performed weekly BP screenings during Banquet mealtimes from August 2021 through December 2022. Basic patient information and BP readings were recorded. Eligible, uninsured patients without PCPs were referred to the Coyote Clinic. Patients were provided educational materials on hypertension and accessing the clinic. Volunteers completed pre- and post-surveys surrounding one year of service assessing comfort level counseling guests, hypertension understanding, and program perception. Volunteers completed pre- and post-surveys assessing comfort level counseling guests and program perception.  Descriptive statistics were used to summarize data.Results: Ninety-six BP readings were recorded from 85 guests, with an average BP of 132/83 mmHg, and 63 guests meeting criteria for Stage 1 hypertension or higher. Forty-two guests were without health insurance and 47 guests without a PCP. Findings revealed 28 hypertensive guests were eligible for referral, with 4 guests agreeing to referral. Another 4 eligible guests agreed to referral for a different ailment. Volunteers reported increased comfort counseling patients and greater understanding of the barriers faced by uninsured persons after volunteering.Conclusions: This study shows that such a referral infrastructure can successfully connect hypertensive patients to a student-run free clinic with the potential to provide significant benefit to patients, otherwise lacking care, for a low cost in resources. Future directions include tracking the number of patients who attend their referral appointment and receive medical treatment, integrating additional preventive health screenings, and involving more organizations affiliated with the target population.